A computational study of the EN 1078 impact test for bicycle helmets using a realistic subject-specific finite element head model. Issue 12 (10th September 2018) - Sandberg, Michael; Tse, Kwong Ming; Tan, Long Bin; Lee, Heow Pueh
Abstract: In the present study, the free fall impact test in accordance with the EN1078 standard for certification of bicycle helmets is replicated using numerical simulations. The impact scenario is simulated using an experimentally validated, patient-specific head model equipped with and without a bicycle helmet. Head accelerations and intracranial biomechanical injury metrics during the impacts are recorded. It is demonstrated that wearing the bicycle helmet during the impact reduces biomechanical injury metrics, with the biggest reduction seen in the metric for skull fracture.